Forever your Earl - Leigh, Eva (Leigh, Eva. Wicked quills of London, 2015)
Eleanor Hawke loves a good scandal. And readers of her successful gossip rag live for the exploits of her favorite subject: Daniel Balfour, the notorious Earl of Ashford. So when the earl himself marches into her office and invites her to experience his illicit pursuits firsthand, Eleanor is stunned. Gambling hells, phaeton races, masquerades. What more could a scandal writer want than a secret look into the life of this devilishly handsome rake? Daniel has secrets, and if 'The Hawk's Eye' gets wind of them, a man's life could be at stake. And what better way to distract a gossip than by feeding her the scandal she desperately craves? But Daniel never expected the sharp mind and biting wit of the beautiful writer, and their desire for each other threatens even his best-laid plans.